Basal forebrain cholinergic system volume is associated with general cognitive ability in the elderly. (October 2018) - Lammers, Florian; Borchers, Friedrich; Feinkohl, Insa; Hendrikse, Jeroen; Kant, Ilse M.J.; Kozma, Petra; Pischon, Tobias; Slooter, Arjen J.C.; Spies, Claudia; van Montfort, Simone J.T.; Zacharias, Norman; Zaborszky, Laszlo; et al.
Abstract: Objective: At the present, it is unclear whether association of basal forebrain cholinergic system (BFCS) volume with cognitive performance exists in healthy as well as in cognitively impaired elderly subjects. Whereas one small study reported an association of BFCS volume with general cognitive ability 'g' in healthy ageing, effects on specific cognitive domains have only been found in subjects with cognitive decline. Here we aim to clarify whether an association of BFCS volume and 'g' is present in a larger sample of elderly subjects without obvious symptoms of dementia and whether similar associations can also be observed in specific cognitive domains. Methods: 282 pre-surgical patients from the BioCog study (aged 72.7 ± 4.9 years with a range of 65–87 years, 110 women) with a median MMSE score of 29 points (range 24–30) were investigated. BFCS and brain volume as well as brain parenchymal fraction were assessed in T1-weighted MR images using SPM12 and a probabilistic map of the BFCS. Neuropsychological assessment comprised the CANTAB cognitive battery and paper-and-pencil based tests. For data analysis, generalised linear models and quantile regression were applied. Results: Significant associations of BFCS volume with 'g' and several cognitive domains were found, with the strongest association found for 'g'. BFCS volume explained less variance in cognitive performance than brain volume. The association was not confounded by brain parenchymal fraction. Furthermore, the association of BFCS volume and 'g' was similar in high- and low-performers. Conclusion: Our results extend previous study findings on BFCS volume associations with cognition in elderly subjects. Despite the observed associations of BFCS volume and cognitive performance, this association seems to reflect a more general association of brain volume and cognition. Accordingly, a specific association of BFCS volume and cognition in non-demented elderly subjects is questionable. Highlights: Cognitive function, BFCS and global brain volume are assessed in 282 elderly patients. Global 'g' has a stronger association with BFCS volume than any cognitive test. Association of BFCS volume and cognition is driven by total brain volume. Relevance of BFCS volume for cognition is independent of global atrophy. Associations of BFCS with dexterity/reaction time are only seen in low-performers.